Who Learns Chemistry Better? Exploring the Role of Resilience and Emotional Intelligence - Dr. Muhammad Siddique; Dr. Muhammad Shabbir Ali; Ammarah Bhatti, (Dialogue Social Science Review (DSSR), 2025)
This study investigated the relationship between emotional intelligence (EI) and resilience among chemistry teachers in Pakistan, examining the effects of demographic variables including gender, teaching experience, locale, and age. Using a quantitative, correlational design, data were collected from 414 chemistry teachers in Lahore via the Siddique & Shabbir Chemistry Resilience Scale (S&S-CRISC) and the Emotional Intelligence Scale (EIS). Pearson correlation results revealed a strong positive relationship between EI and resilience (r = .856, p < .001). Regression analysis showed that EI significantly predicted resilience, accounting for 73.2% of its variance (β = .856, p = .001). Independent sample t-tests indicated significant gender differences, with male teachers scoring higher on both EI and resilience, and significant locale differences for resilience favoring rural teachers. One-way ANOVA results demonstrated significant differences in EI and resilience by teaching experience, but not by age. Findings align with international and national literature, underscoring EI as a key contributor to resilience in the teaching profession. The study highlights the importance of integrating EI training into teacher development programs to enhance resilience, job satisfaction, and educational effectiveness. Further researches may be conducted by adding the one or more variable adopting the mixed-methods or qualitative approach.